Estudo da viabilidade da conversão térmica de resíduos de fibra de média densidade (MDF) - Ferreira, Suelem Daiane (My University, 2014)
Waste Medium density fiberboard (MDF) are generated daily by various sectors, among them stands the furniture sector. Utilization of the MDF waste through thermal conversion can be an alternative to its final disposition. Pyrolysis is one of the most promising technologies for thermal conversion, generating value added products, differentiates it from other renewable energy sources. The products from the pyrolysis process are: char, bio-oil and combustible gases, which have good heating value, with many applications in both chemical industry and in power generation. Knowledge of kinetics was very important in the implementation of the pyrolysis process on a pilot scale reactor by batch. The kinetics of thermal degradation of MDF was evaluated in non- isothermal conditions by means of thermogravimetric analysis (TGA/DTG) in an inert atmosphere (N2), and artificial air (a mixture of N2 and O2). These analyzes were performed with samples of particle diameter less than 0.21 mm and initial mass of 10 mg. For N2 thermogravimetric analysis were used the following heating rate: 5, 10 , 15, 25, 50 , 75 and 100 °Cmin-1, while the artificial tests were conducted with air at a heating rate of 25 °Cmin-1. The experiments on inert atmosphere showed that themain MDF weight loss region occurred between 200 °C and 500 °C, the activation energy ranging from 137 to 152 kJmol-1 , and the pre-exponential factor from 21010 to 51011 min-1. The experiments on artificial air indicated that MDF degradation occurred in three distinct regions: the first ranging from room temperature to 200 °C , the second 200 to 330 °C and finally the third between 350 and 500 °C. However, was in the second region that there was the main mass loss, and the activation energy ranging from 149 to 179 kJ mol-1 and pre-exponential factor of 2.71015 to 3.81016 min- 1. In the third region the activation energy ranged from 144.9 to 155.9 kJmol-1 and pre-exponential factor from 1.3109 to 2.61011 min- 1. The kinetic parameters were determined by non- isoconversionals methods: Coats - Redfern, MacCallum - Tanner, and Van Krevelen. The MDF was characterized by the concentration of metals, minerals, cellulose, hemicellulose, lignin, phenol content, by Scanning Electron Microscopy (SEM), elemental analysis, proximate analysis and heating value . The pyrolysis of MDF was evaluated in a pilot scale reactor by batch with screw conveyor at different heating rates in order to characterize and quantify the products from the pyrolysis process. The char yield ranged between 18.6 and 34.3 (% mass), the of bio-oil yield ranged between 22.9 and 30.2 (% mass ) and of fuel gas yield from 37.3 to 58.6 (% mass). The characterization of the products generated in the pyrolysis process was performed by SEM, FTIR, elemental analysis, proximate analysis, heating value and gas chromatography. An estimate of the overall energy yield of the pyrolysis system used operating at 600 °C indicated a value of 21.8. The energy yield of each one of the reaction products compared to the heating value of the MDF wastes pyrolysed were also estimated: 44.8% in the fuel gas produced; 33.5% in the char produced.
Resíduos de fibra de média densidade (MDF) são gerados diariamente por diversos setores, dentre eles destaca-se o setor moveleiro. O aproveitamento do resíduo de MDF por meio da conversão térmica pode ser uma alternativa para sua disposição final. A pirólise é uma das mais promissoras tecnologias de conversão térmica, gerando produtos de valor agregado, destacando-se de outras fontes de energias renováveis. Os produtos oriundos do processo de pirólise são: o char, bio-óleo e gases combustíveis, que possuem bom poder calorífico, tendo várias aplicações, tanto na indústria química, quanto na geração de energia. O conhecimento de cinética foi fundamental para a implementação do processo de pirólise em um reator de escala piloto de operação semi-contínua. A cinética da degradação térmica do MDF foi avaliada em condições não-isotérmicas através de análises termogravimétricas (TGA/DTG) em atmosfera inerte (N2) e com ar artificial (mistura de N2 e O2). Essas análises foram realizadas com amostras de diâmetro de partícula inferior a 0,21 mm e massa inicial de 10 mg. Para as análises termogravimétricas com N2 foram utilizadas as seguintes taxas de aquecimento: 5, 10, 15, 25, 50, 75 e 100 °Cmin-1, enquanto os ensaios com ar artificial foram conduzidos a uma taxa de aquecimento de 25 °Cmin-1. Os experimentos em atmosfera inerte mostraram que a região onde ocorre a principal perda de massa do MDF acontece entre 200 °C e 500 °C, a energia de ativação variou de 137 a 152 kJmol-1 e o fator pré-exponencial de 21010 a 51011 min-1. Os experimentos com ar artificial indicaram que a degradação do MDF ocorreu em três regiões distintas: a primeira variando da temperatura ambiente até 200 ºC, a segunda de 200 à 330 ºC e a terceira entre 350 e 500 ºC. Entretanto, foi na segunda região que ocorreu a principal perda de massa, sendo a energia de ativação variável entre 149 a 179 kJmol-1 e o fator pré-exponencial de 2,71015 a 3,81016 min-1. Na terceira região a energia de ativação variou de 144,9 a 155,9 kJmol-1 e o fator pré-exponencial de 1,3109 a 2,61011 min-1. Os parâmetros cinéticos foram determinados através dos métodos não-isoconversionais: Coats-Redfern; MacCallum-Tanner; e Van Krevelen. O MDF foi caracterizado quanto à concentração de metais, minerais, celulose, hemicelulose, lignina, teor de fenóis, Microscopia Eletrônica por Varredura (MEV), análise elementar, análise imediata e poder calorífico. A pirólise do MDF foi avaliada em um reator de escala piloto de operação semi-contínua com rosca transportadora visando caracterizar e quantificar os produtos gerados no processo de pirólise em diferentes taxas de aquecimento. O rendimento do char variou entre 18,6 e 34,3 (% massa), o rendimento do bio-óleo variou entre 22,9 e 30,2 (% massa) e o rendimento do gás combustível 37,3 e 58,6 (% massa). A caracterização dos produtos gerados no processo de pirólise foi realizada através de MEV, FTIR, análise elementar, análise imediata, poder calorífico e cromatografia gasosa. Uma estimativa do rendimento energético global do sistema de pirólise empregado operando a 600 ºC indicou um valor de 21,8%. Também foram estimados o rendimento energético de cada produto da reação comparativamente ao conteúdo energético do resíduo de MDF pirolisado: 44,8% no gás combustível produzido; 33,5% no char; e 24,2% no bio-óleo produzido.
Keywords: Madeira -- Produtos; Pirólise